The Implementation and Evaluation of Balance Scorecard in Garuda Chinese Food - Pangestu, Aria Bayu (Journal of Business and Management, 2012)
Garuda Chinese Food has a problem in implementing their strategy. Most of their marketing strategy did not work properly as planned. This condition makes Garuda Chinese Food cannot grow well. After a meeting about this situation, the board of director of Garuda Chinese food agrees that they will try to using a performance measurement system to create new strategies for their restaurant. After a big discussion about this system, the board agrees to make a test using this system and record the data about the effectiveness of this new system. Balanced Scorecard method is the strategic approach and performance management system that can translate the company vision and mission into implementation strategies. The objective of this research is to evaluate the effectiveness of the Balance Scorecard system and prove how this system can generate a new and better strategy then before. The Balance Scorecard is a tool to evaluate the performance of a company. With this evaluation, company can create new strategy that more effective and suitable for their situation. The new strategies that generated by evaluating via Balance Scorecard can increase the company performance. Thus, the performance evaluation of Balance Scorecard is recommended. Keywords: balance scorecard, garuda chinese food, performance management system, effectiveness